EXPLAINING EXISTING PERFORMANCE OF INDONESIA’S AUDIT BOARD: INFORMAL NETWORKS, CONSTITUTIONAL MAKERS’ DECISION, AND CONSTITUTIONAL REFORM - Baidhowah, Adfin Rochmad (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2020)
This study seeks to explain the process of Audit Board article amendment in the constitutional reform as the source of current BPK’s performance, by answering questions: how much do informal networks influence constitutional maker’s decision and to what extent do the external pressures influence the informal networks on the amendment of Audit Board article? This study used a quantitative method to develop variables of social networks in examining how much informal networks based on ideational informal networks influence constitutional makers’ voting between 1999 and 2001 in six meetings which contained voting out of 39 meetings of the Audit Board article amendment. Illustrating statistically significant results of the influence of ideational informal networks on the constitutional makers’ decisions and the influence of high political effect (president’s preference) and strong party pressure on the ideational informal networks, this study shows that “the progressive liberal bloc” which can enforce constitutional reform – particularly Audit Board article though not full-scale reform – within the “ineffective formal institution” as it happened in transition era, has shown how informality’s outcome is in line with formality’s outcome, so it causes improved performance of Audit Board today. Because the statistical evidence talks to broader topics about the people representative bodies and governance, this study suggests paying more attention to the factors of constitutional makers’ networks, on and off the meetings of constitutional reform.